The non-ergodic nature of internal conversion : an experimental and theoretical approach - Scheby Kuhlman, Thomas (Springer Theses, Recognizing Outstanding Ph.D. Research, 2013)
This thesis investigates the transitions from one electronically excited state to another. Such processes - the fastest of events in chemistry - can be studied with femtosecond resolution, and Thomas S. Kuhlman approaches the question both with experimental and theoretical methods. His approach contributes to explain processes of high importance to all scientific fields concerned with the interaction between light and matter: the deactivation of the electronically excited states after excitation. Thomas S. Kuhlman concludes in this thesis that the electronic transition proceeds before the entire set of available degrees of freedom are active - 'It is as simple as that' !